2021
DOI: 10.1080/08995605.2021.1962175
|View full text |Cite
|
Sign up to set email alerts
|

The career transition experiences of military Veterans: A qualitative study

Abstract: Transitioning out of a military career can be difficult and stressful for Veterans. The purpose of this study was to gain an in-depth understanding of the challenges and needs of career transitioning Veterans. Fifteen United States Veterans from a larger mixed methods research project completed a qualitative semi-structured interview regarding their career transition. Interview questions invited participants to define their transition experience, identify influential psychosocial factors, resources utilized or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Perhaps more importantly, when veterans perceive a potentially greater sense of relatedness when they deemphasize the transition, they are more likely to buy into this norm. Given the cultural “stigma” in the military surrounding the transition reported by veterans in the current as well as previous studies (e.g., Shue et al, 2021), it appears important to note that such post-career planning does not have to negatively affect service members’ performance while still in the military. In fact, Lavallee (2019) found that professional athletes, for example, who engage higher levels of post-career planning experience positive effects on team selection (i.e., availability for competition), team tenure (i.e., number of years at their current club), and career tenure (i.e., years competing in their sport overall).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Perhaps more importantly, when veterans perceive a potentially greater sense of relatedness when they deemphasize the transition, they are more likely to buy into this norm. Given the cultural “stigma” in the military surrounding the transition reported by veterans in the current as well as previous studies (e.g., Shue et al, 2021), it appears important to note that such post-career planning does not have to negatively affect service members’ performance while still in the military. In fact, Lavallee (2019) found that professional athletes, for example, who engage higher levels of post-career planning experience positive effects on team selection (i.e., availability for competition), team tenure (i.e., number of years at their current club), and career tenure (i.e., years competing in their sport overall).…”
Section: Discussionmentioning
confidence: 57%
“…Participants further recognized the value of networking and internship programs as factors that helped them regain a sense of competence, which provides two tangible measures that can be used to foster service members’ transition experience and complement considerations, such as finding a new purpose, achieving career satisfaction, and establishing a new identity (Shue et al, 2021) that have been suggested in previous research. As such, the present findings extend knowledge on factors that facilitate a positive transition beyond the primarily personal and service-related factors that cannot be altered when service members prepare to leave the armed forces.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The transition from military-to-civilian life is associated with challenges including identity and employment, establishing meaning and purpose, family and personal relationships, and financial hardship. This can lead to harmful behaviours, including suicide (Danish & Antonides, 2013;Kleykamp et al, 2021;Mobbs & Bonanno, 2018;Morin, 2011;Orazem et al, 2017;Ravindran et al, 2020;Shue et al, 2021). To counter these challenges there is an increasing recognition that military personnel need improved support during the transition from military-to-civilian life.…”
mentioning
confidence: 99%